Strategies to improve alumni engagement / Suriani Norsalim - Norsalim, Suriani (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Alumni engagement is the word used to describe how institutions retain and develop relationships with prior graduates (or alumni) in order to create a powerful professional network. Strategies for involving alumni should begin long before students graduate. Long-lasting networks and more fruitful interactions are facilitated by this. If institutions are offering a mediocre student experience, it will be difficult for them to develop significant interaction with alumni. The basis of a student's relationship with the institution is established long before they become alumni because students only attend college for a (relatively) brief period of time and are alumni for the rest of their lives. While it's quite simple for students to lose their affection for their college, if they didn't enjoy their experience, it's challenging for it to rekindle once they've graduated. Create enduring connections by making existing students feel appreciated and by emphasising that the journey doesn't end when they graduate.